(untitled) (Research, Society and Development, 2022)
In recent years, studies in the agronomic area have intensified in the search for improvements to increase crop production, as well as lower environmental impact. Biopolymers then emerge as an alternative, presenting properties that attracted researchers and producers, especially chitosan, a natural aminopolysaccharide extracted from chitin, characterized as a renewable, low-cost, widely available biopolymer (insect, crustacean and exoskeletons). fungal cell wall), non-toxic, biodegradable and biocompatible. Therefore, this study sought to carry out a literature review on the main findings on the application of chitosan in seeds, especially its action in the germination process of these. For this, searches were carried out in the databases CAPES journal portal, Scielo and Google Scholar, where 14 papers were selected that presented the use of chitosan in seeds of commercial, food and reforestation interest. As a result, it was observed that the biopolymer in question acted as a biostimulant in plant production, improving the growth and development of plants, either through applications in seeds or associated with use after their germination, as well as considerably improving the productivity of several cultures. Therefore, chitosan has an effective performance in the agronomic field with emphasis on application in seeds, being a remarkable alternative to current techniques for using agrochemicals.